Study on bacterial flora in the Hanuman langur (Presbytis entellus) of the Gujarat state, India - Rajesh G. Jani; Saurabh M. Parmar; Rafiyudin A. Mathakiya (Veterinary World, 2013)
Aim: To study the prevalence of bacterial flora in the Hanuman langur (Presbytis entellus) of the Gujarat state Material and Methods: Thirty hanuman langur (Presbytis entellus) (20 male and 10 female), were screened for bacterial flora during the period of June, 2010 to March, 2011. Hanuman langur (Presbytis entellus) were screened by culture of nasal, oral and rectal swabs during routine health monitoring and samples incubated using appropriate media and specific selective culture methods. Bacterial organisms from the normal as well of affected with various diseases and disorders conditions viz. infected wound, electric shock, road accident, jaw injury, stomatitis, respiratory infection and diarrhea were subcultured and identified for genus and species. Results: Significant normal pathogens of the nasal and oral swabs were found mainly Staphylococcus spp., Streptococcus spp., Klebsiella spp., and Proteus spp. whereas from the rectal swabs of hanuman langur the significant pathogen noted were Staphylococcus spp., Streptococcus spp., E. coli spp., Salmonella spp., Proteus vulgaris spp., Klebsiella spp. and Shigella spp. The serotypes of E.coli isolated from rectal swabs of hanuman langur were identified as rough type, O138 and O20. The major antigenic structure of E. coli revealed O138 (10), O20 (6) with rough types (2). Out of the total 10 cases of diarrhea O138 was observed from five isolates while O20 recorded from 3 cases. Out of remained two isolates one isolate of diarrhea revealed rough type and one revealed non typing antigenic structure. Conclusion: The bacteriological prevalence in healthy and infected hanuman langurs in Gujarat reported for the first time inthe current study may serve as a guideline for future studies in the same species. [Vet World 2013; 6(3.000): 131-133]